CHEMICAL TERMINOLOGY IN MODERN UZBEK (Academicia Globe: Inderscience Research, 2021)
This article highlights such problems as the study of modern chemical terminology, which is a large, branched, well-organized system, including terminological units that are very heterogeneous in terms of typological features.